Is the PPP model applicable across sectors? - Armin Riess (EIB Papers, 2005)
Focussing on two key features of a PPP - the bundling of construction and operation of an infrastructure asset, for one, and private ownership for another - this paper argues that the PPP model is suitable for some public services but not for others. While the incentive-oriented mechanism of bundling and private ownership fosters cost savings in the provision of public services, such savings might come at the expense of public-interest objectives, which - after all - set public services apart from private goods and services. The challenge then is to find out whether the conditions for cost savings to outweigh departures from public-interest objectives are more likely to exist for some services than for others. This paper answers affirmatively, putting the ease (or difficulty) of contracting on public services - notably their public-interest objectives - at the heart of the argument.
Keywords: 330; Infrastrukturinvestition; Public-Private Partnership; Öffentliche Dienstleistung